Signifikansi Persekutuan Umat Allah pada Masa Pandemik-Covid 19 - Made Nopen Supriadi; Tony Salurante; Minggus Dilla (SEKOLAH TINGGI AGAMA KRISTEN TERUNA BHAKTI, 2021)
The fellowship of believers in the church faces problems during the Covid-19 pandemic, many Christians have made the Covid-19 pandemic a strong excuse not to go to church. However, after researching the authors found the phenomenon of Christians who do not make fellowship an important part of their spiritual life, it can be seen through the fact that believers are absent from fellowship face-to-face with health protocols and online. Many Christians still have the courage to attend wedding receptions, work at offices, vacations, and eat together at restaurants by applying health protocols. Then Christians are very compulsive and courageous to attend the fellowship in certain moments, namely grief, baptism, confirmation of faith, holy communion, and pastoral counseling. This phenomenon the author identifies as a decline in the understanding of many Christians about the significance of church fellowship. Through this method of theological analysis, this paper will provide a systematic descriptive study of the communion theological principles of the Old and New Testaments. This research provides novelty in the concept of building theological formulation of the community which is not tied to a literal word, but rather to concepts and principles. Through research, believers are reminded to understand the fellowship that God's people make despite the dangers, pressures, threats, and natural disasters. AbstrakPersekutuan orang percaya di gereja mengahadapi masalah pada masa pandemik covid-19, banyak orang Kristen menjadikan pandemik covid-19 sebagai alasan kuat untuk tidak pergi ke gereja. Namun setelah diteliti penulis menemukan fenomena tentang orang Kristen yang tidak menjadikan persekutuan sebagai bagian penting dalam kehidupan rohani, hal itu terlihat melalui fakta ketidak-hadiran orang percaya dalam persekutuan baik secara tatap muka dengan protokol kesehatan dan online. Orang Kristen masih banyak yang memberanikan diri untuk hadir dalam acara resepsi perni-kahan, kerja dikantor, liburan dan makan bersama di rumah makan dengan menerapkan protokol kesehatan. Kemudian orang Kristen dengan sangat terpaksa dan berani hadir dalam persekutuan dalam moment tertentu yaitu kedukaan, baptisan, peneguhan sidi, perjamuan kudus dan pastoral konseling. Fenomena tersebut penulis indentifikasi sebagai merosotnya pemahaman banyak orang Kristen mengenai signifikansi persekutuan gereja. Melalui metode analisis teologis tulisa ini akan memberikan kajian deskriptif sistematis tentang prinsip teologis persekutuan dari Perjanjian Lama dan Perjanjian Baru. Penelitian ini memberikan kebaharuan konsep dalam membangun rumusan teologis tentang persekutuan yang tidak terikat pada kata secara harafiah, tetapi lebih kepada konsep dan prinsip. Melalui penelitian orang percaya diingatkan agar memahami tentang persekutuan yang dilakukan umat Allah meskipun ada dalam bahaya, tekanan, ancaman dan bencana alam.